Coincident keratoconus and Fuchs' endothelial dystrophy: Dual dystrophies mask progression - Wang, Nancy (Indian J Ophthalmol, 2020)
We present an interesting case of a 58-year-old woman who presented coincident keratoconus and Fuchs' endothelial dystrophy. During the 7months following initial presentation, a decline in visual acuity was associated with an apparent improvement in keratoconus, as characterized by corneal tomography parameters, while an increase in corneal pachymetry was also observed. The patient has been managed with left endothelial keratoplasty. This case poses the interesting question of how to classify coincident corneal disease, as traditional parameters for grading the severity of KC are altered by the presence of Fuchs' Endothelial Corneal Dystrophy and vice versa. In such cases, it is important to be aware of coincident disease to more accurately assess progression when considering treatment options and timing.